Retinal changes in multiple sclerosis: An optical coherence tomography and angiography study - Mrabet, S.; Falfoul, Y.; Bouassida, M.; Souissi, A.; El Matri, K.; Gharbi, A.; Chebil, A.; Kacem, I.; El Matri, L.; Gouider, R. (Revue neurologique, 2024)
Multiple sclerosis (MS) is an autoimmune demyelinating disease of the central nervous system with neuroaxonal damage. It is the principal driver of non-traumatic disability in young adults. Visual symptoms are common and optic neuritis (ON) may be the revealing feature in up to 30% of cases. Structural optical coherence tomography (OCT) represents a biomarker of central nervous system neurodegeneration in MS. OCT-angiography (OCT-A) is a noninvasive tool allowing the study of retinal vasculature and the detection of microvascular damage in neuro-retinal diseases. In this study, we aimed to assess structural and microvascular retinal changes in patients with MS with and without ON and to correlate the findings with visual function and MS disability. We conducted a cross-sectional study including patients diagnosed with MS according to the 2017 McDonald criteria. All patients underwent complete neurological examination with evaluation of the Expanded Disability Status Scale (EDSS) and the Multiple Sclerosis Severity Score (MSSS) and an ophthalmological examination including OCT and OCT-A. Patients were compared with age- and sex-matched healthy subjects. The primary endpoints were assessment of retinal nerve fiber layer (RNFL) thickness, ganglion cell layer (GCL+), and ganglion cell complex (GCL++) thicknesses on OCT. Vascular densities in the superficial capillary plexus (SCP), deep capillary plexus (DCP), and choriocapillaris (CC) were assessed on OCT-A, as well as central avascular zone (CAZ) parameters, lacunarity and fractal dimension. A total of 160 MS eyes with and without a previous history of ON and 64 age- and gender-matched healthy eyes were analyzed. Among 160 eyes with MS, 69 had a history of ON. We observed a decrease in RNFL and GCL++ thickness in all 12 quadrants in MS patients when compared to healthy controls. Multivariate analysis by linear regression noted a significant correlation for temporal GCL++ and inferonasal RNFL thickness that were decreased in the MS group. A greater decrease in retinal layers thickness was identified in MS patients with a history of ON. On OCT-A, vascular density in (SCP) was significantly reduced in the MS group (P<0.002). A significant correlation between RNFL thickness and retinal vascular density was found but only in less than half of the hourly quadrants. A significant correlation was noted between visual acuity and CC density (P<0.0001). We also noted an inverse correlation between EDSS scores and CC density (P=0.02 and r=–0.275) and between MSSS and RNFL/GCL++ thicknesses. RNFL and GCL++ layers were thinner in MS patients with a history of ON and were reversely correlated with disease severity. Moreover, retinal vascular changes were observed in MS even in eyes without ON, and CC was reversely correlated with visual function and current disability. Thus, structural OCT coupled with OCT-A could represent a noninvasive and dynamic biomarker of MS severity and progression.